2013
DOI: 10.1051/0004-6361/201321474
|View full text |Cite
|
Sign up to set email alerts
|

Multi-wavelength landscape of the young galaxy cluster RX J1257.2+4738 atz= 0.866

Abstract: Context. Many studies have shown how galaxy properties (e.g. colours, morphology, star-forming (SF) activity, active galactic nuclei population) change not only with redshift, but also with local galaxy density, revealing the important effect of the stellar/halo mass and the environment in the evolution of galaxies. A detailed analysis of the star formation activity in a representative sample of clusters will help us to understand the physical processes that cause the observed changes. Aims. We performed a tho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 91 publications
3
18
0
Order By: Relevance
“…It is unlikely that the observed distributions of SFRs, stellar masses and sSFRs in different environments are extracted from different parent populations, with the evaluated p-value > 0.01 in all cases. The results in this section are consistent with other independent studies at different redshifts (Peng et al 2010;Geach et al 2011;Wijesinghe et al 2012;Koyama et al 2010Koyama et al , 2013bKoyama et al ,a, 2014Feruglio et al 2010;Ideue et al 2012;Muzzin et al 2012;Pintos-Castro et al 2013;Bouché & Lowenthal 2005;Grützbauch et al 2011;Brodwin et al 2013;Hayashi et al 2014;Santos et al 2014;Smail et al 2014). Here, we found no significant evidence that the cosmic web affects the stellar mass, SFR & sSFR of the observed star-forming galaxies at z∼1; a result that might be partially explained by selection biases.…”
Section: The Sfr and Stellar Mass In The Cosmic Websupporting
confidence: 93%
See 1 more Smart Citation
“…It is unlikely that the observed distributions of SFRs, stellar masses and sSFRs in different environments are extracted from different parent populations, with the evaluated p-value > 0.01 in all cases. The results in this section are consistent with other independent studies at different redshifts (Peng et al 2010;Geach et al 2011;Wijesinghe et al 2012;Koyama et al 2010Koyama et al , 2013bKoyama et al ,a, 2014Feruglio et al 2010;Ideue et al 2012;Muzzin et al 2012;Pintos-Castro et al 2013;Bouché & Lowenthal 2005;Grützbauch et al 2011;Brodwin et al 2013;Hayashi et al 2014;Santos et al 2014;Smail et al 2014). Here, we found no significant evidence that the cosmic web affects the stellar mass, SFR & sSFR of the observed star-forming galaxies at z∼1; a result that might be partially explained by selection biases.…”
Section: The Sfr and Stellar Mass In The Cosmic Websupporting
confidence: 93%
“…These results hold at low-z (z 0.5, Fadda et al 2008;Tran et al 2009;Biviano et al 2011;Geach et al 2011;Koyama et al 2011;Mahajan et al 2012 Koyama et al 2008Koyama et al , 2010Sobral et al 2011;Pintos-Castro et al 2013) and high-z (z 1.5, Koyama et al 2014;Santos et al 2014). At z∼1, the closest work to our study in terms of sample selection is that of Sobral et al 2011 who showed that at z∼0.85, the fraction of Hα emitters from both COSMOS-& UDS-HiZELS surveys, when compared to the underlying population of galaxies at the same redshift, peaks at intermediate environments, in agreement with our result.…”
Section: Fraction Of Star-forming Galaxies In the Cosmicmentioning
confidence: 89%
“…Although they are expected to occupy 10% of the volume of the cosmic web, simulations have shown that galaxy filaments contain most of the mass in the universe (∼40%;Aragón-Calvo et al 2010) and host a significant fraction of baryons in the form of a warm-hot intergalactic medium gas in the temperature range 10 5 -10 7 K (Cen & Ostriker 1999Davé et al 2001Davé et al , 2010Klar & Mücket 2012). Filaments are seen in the optical wavelengths as the large-scale thread-like concentration of galaxies (e.g., Pimbblet et al 2004;Scoville et al 2007aScoville et al , 2013Kovač et al 2010;Guzzo & The Vipers Team 2013;Alpaslan et al 2014;Darvish et al 2014Darvish et al , 2015Tempel et al 2014), in X-ray as a warm-hot gas in emission and absorption (e.g., Scharf et al 2000;Zappacosta et al 2002Zappacosta et al , 2010Finoguenov et al 2003;Kaastra et al 2003;Nicastro et al 2005aNicastro et al , 2005bNicastro et al , 2010Werner et al 2008;Danforth et al 2010), in the infrared as possible sites of enhanced star-formation activity, linking clusters (e.g., Koyama et al 2008;Biviano et al 2011;Coppin et al 2012;Pintos-Castro et al 2013), and in the weak-lensing studies as a bridging distribution of dark matter, connecting galaxy clusters (e.g., Dietrich et al 2012;Jauzac et al 2012;Higuchi et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the limited number of studies in this field has already highlighted the importance of filaments as regions with an enhanced fraction of star-forming galaxies and/or star-formation activity (Porter & Raychaudhury 2007;Fadda et al 2008;Koyama et al 2008;Porter et al 2008;Biviano et al 2011;Coppin et al 2012;Pintos-Castro et al 2013;Darvish et al 2014). There are also some systematic surveys/works trying to expand galaxy evolution studies beyond the cluster realm by probing the much larger scale structures (of the order of ∼10 Mpc and beyond) around massive galaxy cluster candidates (see, e.g., Kodama et al 2005;Kartaltepe et al 2008;Lubin et al 2009;Sobral et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, mid-infrared and sub-millimeter wavelength observations have revealed populations of strongly star-forming (ultra-)luminous infrared galaxies (U/LIRGs) in more distant clusters (e.g. Brodwin et al 2013;Pintos-Castro et al 2013;Smail et al 2014;Alberts et al 2014;Santos et al 2014Santos et al , 2015. This enhanced activity means that the mass-normalized integrated star-formation rate for massive clusters evolves rapidly with redshift, Σ(SFR)/M cl ∝ (1+z) α with α as high as seven (e.g.…”
Section: Introductionmentioning
confidence: 99%